A Methodological Modeling of Preparing Future Primary School Educators in Natural Science Instruction in a Multilingual Environment - Gulnaz Kydyrbayeva; Assel Stambekova; Saltanat Abdinazarova; Galiya Kulzhanbekova; Moldir Sultanmurat; Gulvira Matzhanova (Qubahan Academic Journal)
This study focuses on the development and implementation of a comprehensive methodological model aimed at preparing future primary school educators for effective natural science instruction within the unique context of a multilingual environment. The research delves into the intricate intersection of science education, acknowledging the increasing multicultural landscape of primary classrooms. The methodological model is designed to address the specific challenges posed by multilingual settings, emphasizing the cultivation of educators’ professional competencies in navigating and delivering impactful natural science content. This study presents a comprehensive model for preparing future primary school educators to teach natural science in multilingual classrooms, focusing on developing professional competencies to address these unique challenges. It explores theoretical foundations, practical strategies, and pedagogical tools to enhance educators’ effectiveness in fostering students' understanding of natural science in multicultural environments. The outcomes of this research contribute valuable insights into enhancing the professional preparation of future primary school educators, fostering their ability to foster a meaningful understanding of natural science among students in multilingual educational settings.